Non-familial paid caregivers as potential flu carriers and cause of spread: the primary prevention of flu measured through their adhesion to flu vaccination campaigns—A Florentine experience. Issue 10 (3rd October 2019) - Bonaccorsi, Guglielmo; Pieralli, Francesca; Innocenti, Maddalena; Milani, Chiara; Del Riccio, Marco; Bechini, Angela; Boccalini, Sara; Bonanni, Paolo; Lorini, Chiara
ABSTRACT: Introduction : Influenza vaccination is recommended for caregivers of elderly people. In a study aimed at assessing the level of health literacy (HL) in a sample non-familial caregivers in the Florence Health District (Tuscany), data were collected regarding access and adherence to the flu vaccination campaigns. Methods : The sample consists of 47 non-familial paid caregivers. We collected information regarding socio-demographic characteristics, services provided and daily work time, whether or not influenza vaccination was administered for the 2016/2017 season and in the previous three years. The level of HL was assessed through the Newest Vital Sign. Results : 63.8% of non-familial caregivers have not joined the flu campaigns over the last four years, 14.9% have been vaccinated only sometimes (in some epidemic seasons), and 21.3% have received a flu shot in all the seasons investigated. Most of the non-familial caregivers who do not get vaccinated (27.7%) do not perceive that they are in direct contact with a person at-risk; those who get the vaccine regularly (12.8%) reported they want to protect the assisted person as motivation for vaccine uptake. Vaccination was not associated with HL. Conclusion : Adhesion to anti-flu vaccination campaigns for these homecare workers has been resulted rather poor. Coverage does not seem to be related with HL level. It seems appropriate to promote extensively flu vaccination among family carers by actively offering the vaccination in appropriate forms, places and times, to avoid serious consequences on elderly people with higher risk of comorbidity and frailty.